On the scent : a journey through the science of smell - Pelosi, P. (Oxford University Press, 2016)
Smell is arguably the most evocative of senses, linked to memories and associations. For most animals it is vital for survival. For us, it enriches our experience of the world, our pleasure in food and drink, and affects all human interaction. Paolo Pelosi describes how scientists are finally unravelling the science of smell.